(untitled) (Research, Society and Development, 2021)
The environmental concern with the residues generated by the textile industry’s productive processes encouraged the development of research in the area. The development of new materials from the waste generated by it is an alternative to dispose of all the accumulated material, thus adding a new application. As the construction sector also plays an important role in relation to environmental degradation in the urban environment, the search for materials aimed at sustainability in the sector is growing, requiring several researches that seek the development of new materials for the sector. In view of these considerations, it was sought to develop an alternative material from polyester residues incorporated in a recycled polymer matrix. The obtained materials were characterized by Granulometry and SEM, making it possible to identify their properties and define which is the best methodology to be used for making the specimens. Then composite materials were prepared using different polyester incorporations (10%, 20%, 30%, 40% and 50%) in relation to the recycled polypropylene matrix. With the analysis of the tensile tests it was possible to determine that the best results obtained occurred considering the incorporation of 16.5% of fiber in the recycled polypropylene matrix, given this confirmed by subsequent tensile and impact tests.